Comparison of orbital fibroblasts from Graves’ ophthalmopathy and healthy control - Yu Wu; Jiuming Zhang; Wen Deng; Chaoting Mo; Yumei Liang; Kongqian Huang; Fan Xu; Fen Tang (Heliyon, 2024)
Graves' ophthalmopathy (GO) is an extrathyroidal manifestation of Graves' disease, Orbital fibroblasts (OFs) are recognized as key players in GO pathogenesis, involved in orbital inflammation, tissue remodeling, and fibrosis. This study offers a primary exploration of cell behavior and characteristics on OFs from GO (GO-OFs), and compared to OFs from healthy control (HC-OFs). Results reveal that GO-OFs exhibit delayed migration from tissue fragments, while no significant difference in cell proliferation is observed between GO-OFs and HC-OFs. Aberrant expression pattern of surface proteins Thy-1, TSHR, and IGF-1R suggests shared autoantigens and pathways between GO and GD, contributing to inflammation and fibrosis. Investigations into cytokine responses unveil elevated secretion of hyaluronic acid (HA) and prostaglandin E2 (PGE2) in GO-OFs, emphasizing their role in tissue remodeling. These findings deepen our understanding of OFs in GO pathogenesis, offering potential therapeutic avenues.